2004
DOI: 10.1103/physrevd.70.121502
|View full text |Cite
|
Sign up to set email alerts
|

Are there hyperentropic objects?

Abstract: By treating the Hawking radiation as a system in thermal equilibrium, Marolf and R. Sorkin have argued that hyperentropic objects (those violating the entropy bounds) would be emitted profusely with the radiation, thus opening a loophole in black hole based arguments for such entropy bounds. We demonstrate, on kinetic grounds, that hyperentropic objects could only be formed extremely slowly, and so would be rare in the Hawking radiance, thus contributing negligibly to its entropy. The arguments based on the ge… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

14
654
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 366 publications
(671 citation statements)
references
References 23 publications
(37 reference statements)
14
654
1
Order By: Relevance
“…This result has been generalised to standard scalar-tensor theories [9] (see also earlier work by Bekenstein with the extra assumption of spherical symmetry [10,11]). …”
mentioning
confidence: 99%
“…This result has been generalised to standard scalar-tensor theories [9] (see also earlier work by Bekenstein with the extra assumption of spherical symmetry [10,11]). …”
mentioning
confidence: 99%
“…For the case of black holes, as already said above, Bekenstein was the first to state that the adiabatic invariants are the black hole horizon areas [9,10]. Exploiting the idea of adiabatic invariants and the statement by Bekenstein [8], Kunstatter [11] derived for the d(≥ 4)-dimensional Schwarzschild black hole an equally spaced entropy spectrum.…”
mentioning
confidence: 99%
“…However, it was proven by Bekenstein [8,9] and others [15,16] that the area spectrum of Kerr black hole is discrete and uniformly spaced. Therefore, it was concluded that the function that was used in the above-mentioned computation as real part of the asymptotic quasinormal frequencies of Kerr black hole, i.e.…”
mentioning
confidence: 99%
“…Consequently, they argued that the BEB does not have to be postulated as a separate requirement in addition to the GSL. Responding to their arguments Bekenstein [4] has argued that it is not always obvious in a particular example how the system avoids violating the bound and analyzed in detail several of the purported counterexamples of this type and demonstrated in each case the specific mechanism enforcing the bound.…”
Section: Introduction a What Are Entropy Bounds?mentioning
confidence: 99%